2016
DOI: 10.1038/modpathol.2016.80
|View full text |Cite
|
Sign up to set email alerts
|

p16/Ki-67 dual-stained cytology for detecting cervical (pre)cancer in a HPV-positive gynecologic outpatient population

Abstract: Women who test positive for a high-risk type of the human papillomavirus (HPV) require triage testing to identify those women with cervical intraepithelial neoplasia grade 3 or cancer (≥ CIN3). Although Pap cytology is considered an attractive triage test, its applicability is hampered by its subjective nature. This study prospectively compared the clinical performance of p16/Ki-67 dual-stained cytology to that of Pap cytology, with or without HPV16/18 genotyping, in high-risk HPV-positive women visiting gynec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 36 publications
6
55
0
3
Order By: Relevance
“…In these studies, p16/Ki-67 dual-stained cytology had a consistently high sensitivity for ≥CIN3 (86.9-93.8% which was comparable to that of Pap cytology [65][66][67]. The specificity for ≥CIN3 of p16/Ki-67 dual-stained cytology was estimated at 51.2% [67] to 56.9% [65], which is high compared to Pap cytology (44.9% [67] to 48.7% [65]). Because p16/Ki-67 dualstained cytology can be adequately interpreted by relatively untrained staff, it has a decreased interobserver variability compared to Pap cytology [68,69].…”
Section: P16/ki-67 Dual-stained Cytologymentioning
confidence: 58%
See 4 more Smart Citations
“…In these studies, p16/Ki-67 dual-stained cytology had a consistently high sensitivity for ≥CIN3 (86.9-93.8% which was comparable to that of Pap cytology [65][66][67]. The specificity for ≥CIN3 of p16/Ki-67 dual-stained cytology was estimated at 51.2% [67] to 56.9% [65], which is high compared to Pap cytology (44.9% [67] to 48.7% [65]). Because p16/Ki-67 dualstained cytology can be adequately interpreted by relatively untrained staff, it has a decreased interobserver variability compared to Pap cytology [68,69].…”
Section: P16/ki-67 Dual-stained Cytologymentioning
confidence: 58%
“…Although data on the long-term ≥CIN3 risk in p16/Ki-67 dual-stain negative women are currently lacking, results from the studies with short-term follow-up (up to 2 years) [65] are promising, reporting NPVs of a single p16/Ki-67 dual-stained cytology test between 97.4% and 99.4% [65,67]. In a population-based screening cohort, Wentzensen et al found a PPV of 12.4% [65], whereas in an outpatient population Luttmer et al found a PPV of 29.9% [67].…”
Section: P16/ki-67 Dual-stained Cytologymentioning
confidence: 94%
See 3 more Smart Citations